Prevalence of Malocclusion in 13-15 Year-old Adolescents in Tabriz - Mohammad Hossein Ahangar Atashi (Tabriz University of Medical Sciences, 2007)
Background and aims. Malocclusion with its great hazardous effects seems to have become more prevalent in recent decades; therefore, the present study was carried out to assess the prevalence of different malocclusions among 13-15 year-old adolescents in Tabriz. Materials and methods. The subjects in the present study consisted of 398 adolescents aged 13-15, who were randomly selected from 5 different districts of the city. Students who had previous orthodontic treatment or extraction of any permanent teeth were excluded from the study. Angle's classification was used to describe the type of malocclusion and the evaluation of other aspects of malocclusion such as overjet, overbite and crowding were considered the minor goals of the study. The prevalence of different types of malocclusion in the population under study was estimated. Results. According to the results of the study, only 4% of 13-15 year-old adolescents under study had normal occlusion, whereas 51% had Class I, 21.9% had Class II [17.6% div 1, 4.3% div 2] and 17.1% had Class III malocclusion. With respect to overjet, the study revealed that 30.7% of the population under study had increased overjet, 33.9% had decreased overjet and 2% had reverse overjet. Increased overbite was observed in 40.2% of the population studied, whereas decreased overbite was found in 19.3%, deep bite was noted in 3.3% and open bite was detected in 3.3% of the studied population. Conclusion. Class I malocclusion was the most prevalent, whereas Class III malocclusion was the least prevalent among adolescents aged 13-15 in Tabriz.